2005
DOI: 10.1007/s00534-005-0991-2
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic colon cancer from intrahepatic cholangiocarcinoma

Abstract: A 62-year-old man had been followed because of an elevated serum level of carcinoembryonic antigen without the detection of any cancer lesions. However, there was a sudden increase in the serum level of carcinoembryonic antigen, and abdominal imagings showed a hepatic tumor with peripheral intrahepatic bile duct dilatation, and a submucosal tumor at the sigmoid colon with intact mucosa. Histopathological findings showed that the hepatic tumor had perineural invasion, suggesting an intrahepatic cholangiocarcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
1
10
1
Order By: Relevance
“…Previous studies have not reported the metastasis of CC into the colon in domestic and wild animals (Lepri et al 2013). In humans, however, CC may metastasise, although rarely, into the colon (Wakahara et al 2005). We also observed, unlike other studies, metastasis of the CC into the caecum and ileocecal area.…”
Section: Discussioncontrasting
confidence: 54%
“…Previous studies have not reported the metastasis of CC into the colon in domestic and wild animals (Lepri et al 2013). In humans, however, CC may metastasise, although rarely, into the colon (Wakahara et al 2005). We also observed, unlike other studies, metastasis of the CC into the caecum and ileocecal area.…”
Section: Discussioncontrasting
confidence: 54%
“…Until now, unusual metastastic sites from cholangiocarcinoma were reported to be the colon, adrenal gland, skull bone, epididymis, corneal limbus, meninges, ovary, skeletal musle, and skin 2,8-15. Metastasis of a distal cholangiocarcinoma to the stomach has not been reported previously to our knowledge but, as in the above-mentioned sites, appears to be a rare site of metastasis of this tumor.…”
Section: Discussionmentioning
confidence: 78%
“…Although it comprises only 10-15% of all hepatobiliary neoplasms, its incidence is increasing 1. Frequent metastatic sites of biliary cancer are the liver, peritoneum, intra-abdominal lymph nodes, and lungs 2. Here, we describe a very rare case in which metastatic cholangiocarcinoma of the stomach was mistaken for primary gastric cancer in a patient who underwent Whipple's operation.…”
Section: Introductionmentioning
confidence: 89%
“…The recurrence patterns include intrahepatic recurrence, peritoneal dissemination, lymph nodes metastasis, and remote organ metastasis to sites such as lung and bone [3][4][5]. A solitary colon metastasis from ICC is unusual: To our knowledge, there are only two published reports of a solitary colon metastasis from ICC [6,7]. One case was synchronous, and the other was metachronous, occurring 5 years after resection of the primary tumor.…”
Section: Discussionmentioning
confidence: 78%